P191Mivrovascular damage, endothelium dysfunction and angiogenesis biomarkers as predictors of digital ulcers in systemic sclerosis. (15th July 2014) - Silva, DR; Vasconcelos, C
Abstract: Background: Digital Ulcers (DU) are a major disabling complication of SSc that interferes seriously with personal and professional life of our patients. The aim of this study was to correlate functional dysfunction of endothelium, capillaroscopy and angiogenesis biomarkers in patients with SSc in order to try to predict the development of digital ulcers in these patients. Methods: This is a prospective study of patients with Systemic Sclerosis (SSc) and primary Raynaud Phenomenon (RP) attending our Raynaud Clinic: n= 108. Demographic and epidemiological data, Flow mediated dilation (FMD) and end diastolic volume (EDV), capillaroscopy, Endothelin-1 (ET-1), ADMA, VEGF and Endoglin were analyzed and compared to a control group (n=31). Statistical calculations were performed using SPSS (v 20.0). Comparison and distribution between groups were performed using Kruskal-Wallis test. The Mann-Witney test was used to compare continuous variables wit nominal variables. A p value ≤ 0.05 was considered significant. Results: Flow mediated dilation (FMD) had statistical differences (P<0.001) between SSc patients with digital ulcers compared to SSc patients without DU or primary Raynaud phenomenon (RP). End diastolic volume was significantly different between groups (P<0.001) suggesting an increase in peripheral resistance in patients with DU. FMD was more reduced in patients with late pattern (Cutolo classification) in capillaroscopy and a statistical differences (P<0.001) between early and late pattern (P<0.007) was found. Endothelin-1 and ADMA were increased in patients with DU (P<0.001) which might explain an excessive vasoconstrictor tone in these patients in association with occlusion of distal digital circulation (avascular areas in capillaroscopy) leading to the reduced FMD in patients with DU. VEGF was increased in SSl patients without DU, we found no difference with primary RP (P<0.168). A statistical differences (P<0.002) between patients with DU and SSc patients with no DU or with primary RP was found in VEGF. Endoglin was increased in patients with DU (p<0, 001). Patients with Cutolo late pattern in capillaroscopy had a increase in the angiostatic biomarker endoglin in comparison with the other groups (p<0, 005). Conclusion: In our study, patients with antibody Sscl 70 positive, decreased FMD and low EDV, late pattern of Cutolo classification, increased ET-1, ADMA and endoglin and a reduced VEGF were at higher risk of developing digital ulcers.